UMP mosque rental inventory management system - Aina Umairah, Mazlan (2018)
Nowadays in the era of Information and Communication Technology (ICT), it has been predicted that computerized booking will provide more convenience to people and they can make booking anytime and anywhere with the access of internet. Universiti Malaysia Pahang (UMP) provide with the latest ICT systems which includes Wi-Fi internet connections to make ease of university electronic based e-Learning and e-Management activities. Now in the UMP, there are some process need to be through manually, one of it is booking for facilities and services at the UMP mosque. Currently Pusat Islam & Pembangunan Insan (PIMPIN) is using paper-based booking which this lead to many difficulties especially for the management process. The staff not only need to manage the booking but also the equipment and services which need to be sure that all the equipment borrowed is enough and in a good condition. Thus, all these booking and inventory information need to be recorded in an efficient and effective way. UMP Mosque Rental Inventory Management System is an online system for booking facilities and equipment provided at the UMP mosque. This system is developed for desktop and mobile version. The objective for this project are to study the requirement on UMP Mosque Rental Inventory Management System, to design and develop a prototype of UMP Mosque Rental Inventory Management System based on structured technique and to evaluate the proposed system. This project was implemented using Rapid Application development (RAD) methodology. This methodology is suitable for this project because it require short time development. As a result, this project had successfully been developed within the given time. This system already undergo several testing to ensure that this system meet all requirement and achieve user satisfaction. But there is still have some functionality need to add and upgrade in this system in future such as user can make online payment for the booking user able to choose the language to be used in this system. In a nutshell, UMP Mosque Rental Inventory Management System can help people make booking faster and easier. Also help PIMPIN to improve record management for booking and UMP mosque inventory effectively.